2015
DOI: 10.1021/acs.inorgchem.5b00988
|View full text |Cite
|
Sign up to set email alerts
|

Prospecting Lighting Applications with Ligand Field Tools and Density Functional Theory: A First-Principles Account of the 4f7–4f65d1 Luminescence of CsMgBr3:Eu2+

Abstract: The most efficient way to provide domestic lighting nowadays is by light-emitting diodes (LEDs) technology combined with phosphors shifting the blue and UV emission toward a desirable sunlight spectrum. A route in the quest for warm-white light goes toward the discovery and tuning of the lanthanide-based phosphors, a difficult task, in experimental and technical respects. A proper theoretical approach, which is also complicated at the conceptual level and in computing efforts, is however a profitable complemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 61 publications
4
35
0
Order By: Relevance
“…57 DFTbased cluster calculations recently showed that this is a reasonably good assumption even if the ionic radii of the alkaline earth and lanthanide ions differ a lot. 61,67 The dependence on the metal-ligand distance is weak compared to expectations from classical crystal field theory (r À5 dependence), but gets closer to the estimations of the chemical shift model of Dorenbos attempted for Ce 3+ or Eu 2+ (r À2 dependence). 68 We found an r À1.2 dependence of 10 Dq of Yb 2+ for the halides CsMX 3 .…”
Section: Effect On Crystal Field and Exchange Splittingsupporting
confidence: 73%
See 1 more Smart Citation
“…57 DFTbased cluster calculations recently showed that this is a reasonably good assumption even if the ionic radii of the alkaline earth and lanthanide ions differ a lot. 61,67 The dependence on the metal-ligand distance is weak compared to expectations from classical crystal field theory (r À5 dependence), but gets closer to the estimations of the chemical shift model of Dorenbos attempted for Ce 3+ or Eu 2+ (r À2 dependence). 68 We found an r À1.2 dependence of 10 Dq of Yb 2+ for the halides CsMX 3 .…”
Section: Effect On Crystal Field and Exchange Splittingsupporting
confidence: 73%
“…A clear assignment of all states can only be attempted upon inclusion of the full Hamiltonian, as performed by the theoretical approaches mentioned above. 33,35,36,60,61 However, it becomes clear from the spectra that the decoupled scheme affords very reasonable results in a simple manner and without calculation, which is particularly important for experimentalists.…”
Section: Fine Structure Of the Excitation Spectramentioning
confidence: 99%
“…58 Recently, advances have been made by using ligand field density functional theory (LFDFT) to describe the 4f 7 good agreement. 59 Although useful, the computational cost of these calculations preclude HT computations from predicting the optical properties on a large scale.…”
Section: +mentioning
confidence: 99%
“…In recent years, spectroscopic properties of divalent lanthanide elements (Ln 2+ ) have been intensively studied, both experimentally and theoretically . However, electronic spectroscopy of divalent neodymium still remains practically an unexplored area.…”
Section: Introductionmentioning
confidence: 99%